The Effect of Realistic Mathematic Approach on Students’ Learning Motivation - Lestari, Shindy; Syahrilfuddin, Syahrilfuddin; Putra, Zetra Hainul; Hermita, Neni (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2019)
This research is to determine the effect of realistic mathematical approach on students’ learning motivation. The research method is pre-experiment of one group pretest posttest design. This study was conducted with 34 fifth grade students from a public school in Pekanbaru, Indonesia. The results indicate that students’ learning motivation significantly increases. Among six indicators measuring students’ learning motivation, the indicator of interesting activities in learning is the most increase, from 80.76% in pre-test to 86.40% inpost-test. The average score of pretest in form of students’ learning motivationquestionnaire before applying treatment was 90.56 while score posttest after treatment was 95,09 and the results of the research hypotheses using the comparative t-test tcount (6.997) > ttable (2.039). This means that there is an effect of applying the realistic mathematical approach to students’ learning motivation.